The Association of the Bride and Groom After Performing Khitbah and the Role of Parents in It - Kadir, Mukhlis Abd. (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2022)
Before proceeding to marriage, there are stages that can be taken before the marriage contract is carried out, one of which is the sermon (engagement), which is to prepare for the future marriage process, which is not legal according to Islamic law, but aims to find out the personalities of both parties. This article aims to explain how the bride and groom interact after performing the sermon and the role of parents in it in Islamic family law. The interaction between the bride and groom which gives rise to various interactions that require regulation is called an-nizham alijtima'i. This system essentially regulates interactions between two opposite sexes (men and women) and regulates various interactions that arise from these interactions. The data collected comes from articles, journals, books and working papers. The results of the research are that the engagement period is not the same as the period after marriage. In principle, during the engagement period, there are no legal consequences like husband and wife. During this engagement period, it is only for ta'aruf (introduction) between the two parties and preparations before the wedding, that is why in social relations you must prioritize Islamic ethics, therefore the prospective bride and groom are still the responsibility of their respective parents. each in terms of the relationship between the two.